Teachers’ Strategies in Managing Classroom through Integration of Canva Audiovisual Media in English Speaking Learning - Nurlinda; Nurdin Noni; Abdullah (International Journal of Language, Education, and Literature, 2025)
This qualitative study explores classroom management strategies used by English teachers using Canva-based audiovisual media to improve students' English speaking skills. Conducted at IMMIM Boys' Islamic Boarding School Makassar, this study investigated how Canva—an educational design platform—was integrated into speaking activities to increase classroom engagement and interaction. Using a descriptive case study approach, data were collected through in-depth interviews, classroom observations, and documentation. Participants included one English teacher and ten eighth-grade students. The study findings revealed that effective classroom management involves a combination of clear rules, efficient time allocation, flexible seating arrangements, and differentiated learning strategies supported by Canva's visual and audio features. This study contributes to the understanding of how digital tools such as Canva can meaningfully interact in classroom management and English language teaching. It offers insights for educators who want to modernize their teaching methods using technology-based strategies.